The Use of SCORM Specification in Designing Reusable Learning Content - Aida Liza, Hussin (2005)
The widespread use of WWW for educational purposes creates opportunities in reusing educational materials. In the past, most of the learning materials are created for a specific purpose in a specific context such as for military training, employees’ supervisions, and training community. The way of designing this material restricted the material to be reusable in other educational purpose. Besides, the need for a standard in designing reusable learning material helps to produce quality e-learning experiences. SCORM is a set of specifications for developing, packaging, and delivering high quality educational and training materials whenever and wherever it is needed. The use of SCORM specification in designing and reusing learning material impacted the development of potential and good SCORM-compliant learning material. Therefore, this research is undertaken to produce a process model in designing reusable learning content. Existing material is redesigned based on the proposed process model in order to increase the reusability of the learning material. A Test Suite was used to determine the conformance of developed learning content to the SCORM Specification. Based on the results, a list of needed elements to develop SCORM-compliant content was outlined. The steps used in the learning content development process model can be used as a guideline in creating a quality learning material that can be shared among other LMS. Together with the use of XML technology, it opens a wide spectrum of possibilities for design and presentation of high quality materials for a particular education or training purpose and plays an important role in the exchange of wide variety of data on the Web.